Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Efektivitas Pendistribusian Sedekah di Kota Bogor - Khaerani, Aulia Nisa; Abidin, Yusuf Zaenal (Tadbir: Jurnal Manajemen Dakwah, 2023)
This study aims to determine the process of recruitment and placement, development or training, and evaluation of human resources in increasing the effectiveness of alms distribution in the philanthropic institution Aksi Cepat Tanggap (ACT) Bogor City Branch. This study uses a descriptive research method with a qualitative approach. The results of this study indicate that the initial recruitment and placement process sets short and long-term goals, after placing volunteers according to their place of residence and the cluster they choose. The development or training has not implemented because it is still improving the core management of the Indonesian Volunteer Society (MRI). Evaluation of human resources with volunteer schedules, volunteer needs, goals and target programs, as well as maintaining institutional independence values.